2017
DOI: 10.1016/j.devcel.2017.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Mps1 Regulates Kinetochore-Microtubule Attachment Stability via the Ska Complex to Ensure Error-Free Chromosome Segregation

Abstract: SUMMARY The spindle assembly checkpoint (SAC) kinase Mps1 not only inhibits anaphase but also corrects erroneous attachments that could lead to missegregation and aneuploidy. However, Mps1’s error correction-relevant substrates are unknown. Using a chemically tuned kinetochore-targeting assay, we show that Mps1 destabilizes microtubule attachments (K-fibers) epistatically to Aurora B, the other major error-correcting kinase. Through quantitative proteomics, we identify multiple sites of Mps1-regulated phosphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
94
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(107 citation statements)
references
References 96 publications
(186 reference statements)
12
94
1
Order By: Relevance
“…At low Ska1 complex concentration, we observed that individual molecules associated with and tracked the microtubule plus end only briefly, indicating that this tracking is not highly processive (Figure 3B). Additionally, although work from others has not detected plus end tracking of elongating microtubules by the Ska1 complex [13], we observed a notably increased brightness for GFP-Ska1 complex fluorescence at growing microtubule ends (Figure 3B; Figure S3C; Movie S1) indicative of plus end tracking with microtubule polymerization.…”
Section: Resultscontrasting
confidence: 51%
See 1 more Smart Citation
“…At low Ska1 complex concentration, we observed that individual molecules associated with and tracked the microtubule plus end only briefly, indicating that this tracking is not highly processive (Figure 3B). Additionally, although work from others has not detected plus end tracking of elongating microtubules by the Ska1 complex [13], we observed a notably increased brightness for GFP-Ska1 complex fluorescence at growing microtubule ends (Figure 3B; Figure S3C; Movie S1) indicative of plus end tracking with microtubule polymerization.…”
Section: Resultscontrasting
confidence: 51%
“…In addition, although the Ska1 MTBD is necessary and sufficient for Ska1 complex microtubule binding and spindle localization [2], we note that recent work has also suggested a contribution to microtubule interactions from Ska3 [28]. Ultimately, these activities must be regulated [13, 29, 30] and integrated with other players at the kinetochore, including the Ndc80 complex [2, 31, 32], to ensure faithful chromosome segregation during every cell division.…”
Section: Resultsmentioning
confidence: 99%
“…S1A-D). Cell extracts were prepared by nocodazole treatment, mitotic shakeoff, and nitrogen cavitation as described [3,23,34] and immunoprecipitated with Zw10-specific antibodies. Samples were resolved by All was not peer-reviewed) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.…”
Section: Declaration Of Interestsmentioning
confidence: 99%
“…3C). We identified two Mps1 phosphorylation sites at the N-terminus of Rod (T13 and S15), upstream of its beta-propeller domain [23]. To test their function, wildtype (WT) and nonphosphorylatable (2A) Rod were expressed in T-Rex FLP-in HeLa cells as LAP (EGFP-TEV-S-peptide) fusions (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation